Workplace culture must emphasise mutual respect [in Chinese] - ONG, Siow-heng (Institutional Knowledge at Singapore Management University, 2023)
In a commentary, SMU Professor of Communication Management (Education) Ong Siow Heng discussed the importance of having a respectful culture in the workplace. He opined that one way to appreciate employees is to provide equitable pay and career advancement opportunities for staff, so that workers will know that their employer respects their contribution. Even though more forms of disrespect for workers are being addressed by law, Prof Ong opined that improving respect for the workers’ dignity is best managed by those in workplace leadership even before relevant laws are passed, especially in areas that cannot be covered by law. He added that it is important for employers and the public to value the employees and help them retain their dignity. This will help create a dignified and caring community. [Article in Chinese]